Influences of Dietary Added Sugar Consumption on Striatal Food-Cue Reactivity and Postprandial GLP-1 Response - Dorton, Hilary M.; Luo, Shan; Monterosso, John R.; Page, Kathleen A. (Frontiers in Psychiatry, 2018)
Sugar consumption in the United States exceeds recommendations from the American Heart Association. Overconsumption of sugar is linked to risk for obesity and metabolic disease. Animal studies suggest that high sugar diets alter functions in brain regions associated with reward processing, including the dorsal and ventral striatum. Human neuroimaging studies have shown that these regions are responsive to food cues, and that the gut-derived satiety hormones, glucagon-like polypeptide-1 (GLP-1), and Peptide YY (PYY), suppress striatal food cue responsivity. We aimed to determine the associations between dietary added sugar intake, striatal responsivity to food cues, and post-prandial GLP-1 and PYY levels. Twenty-two lean volunteers underwent a functional magnetic resonance imaging (fMRI) scan during which they viewed pictures of food and non-food items after a 12-hour fast. Prior to scanning, participants consumed a glucose drink. A subset of 19 participants underwent an additional fMRI session in which they consumed water as a control condition. Blood was sampled for GLP-1 and PYY levels and hunger ratings were assessed before and 75 minutes after drink consumption. In-person 24-hour dietary recalls were collected from each participant on 3 to 6 separate occasions over a two-month period. Average percent calories from added sugar was calculated using information from 24-hour dietary recalls. A region-of-interest analysis was performed to compare the blood oxygen level dependent (BOLD) response to food vs. non-food cues in the bilateral dorsal striatum (caudate/putamen) and ventral striatum (nucleus accumbens). The relationships between added sugar, striatal responses, and hormone changes after drink consumption were assessed using Spearman’s correlations. We observed a positive correlation between added sugar intake and BOLD response to food cues in the dorsal striatum and a similar trend in the nucleus accumbens after glucose, but not water, consumption. Added sugar intake was negatively associated with GLP-1 response to glucose. Post-hoc analysis revealed a negative correlation between GLP-1 response to glucose and BOLD response to food cues in the dorsal striatum. Our findings suggest that habitual added sugar intake is related to increased striatal response to food cues and decreased GLP-1 release following glucose intake, which could contribute to susceptibility to overeating.